Comparison of devotilization rates of Philippine coal under pyrolytic conditions - Dugos, Nathaniel P. (Animo Repository, 1997)
The effects of coal rank or type, temperature, residence time and reactor type on the devolatilization of Philippine coal samples was investigated and analyzed. Pyrolysis of the coal samples was conducted up to 700 degrees Centigrade using the Closed-Type Thermobalance Reactor and thermogravimetric Analyzer. Results indicated that Cagayan coal showed the highest weight loss followed by Samar coal then Surigao coal and Zamboanga coal, the lowest. This behavior is consistent at all hold temperatures. Faster rate of devolatilization was observed between 0 to 15 minutes at hold temperatures at 500, 600 and 700 degrees Centigrade for all coal samples studied except Zamboanga coal. Also, an increase in volatilization rate occurred when the hold temperature was increased. Further, the Thermogravimetric Analyzer experimental results showed significantly higher weight losses and yield of char than those obtained using the Closed-Type Thermobalance Reactor.